Turning ideas into research : theory, design & practice - Fawcett, Barbara, 1955-; Pockett, Rosalie (Los Angeles : SAGE, 2015)
How do you turn a really good idea into a really good question, and how do you turn this into successful research? Barbara Fawcett and Rosalie Pockett use their expertise as supervisors and researchers to provide you with the frameworks and the theoretical and practical guidance you need to design, carry out and communicate your research effectively. Using a range of examples that relate research to the real world, they demonstrate: *how to develop research questions *how to select appropriate theoretical frameworks *how to integrate theoretical perspectives with empirical research *how to gather and interpret data *how to ensure that the research undertaken makes a difference. The authors' user-friendly approach emphasizes the importance of participation, collaboration and inclusivity, and examines worldviews and understandings of knowledge in order to enable greater critical reflection. Chapters provide guidance on achieving impact with your research, and feature reflective questions to enhance your engagement with the issues covered. This text is the ideal companion as you set about transforming your ideas into robust research.--
Includes bibliographical references (pages 153-165) and index.
Text in English.
Keywords: Research -- Methodology